The Effectiveness of Two Writing Portfolios on High School Students’ Writing Achievement - Atmarita Atmarita; Mohammad Adnan Latief; Utari Praba Astuti (Pascasarjana UM, 2021)
Abstract: Writing in English teaching and learning is perceived as a difficult skill due to internal and external factors. This study investigated the effectiveness of two writing portfolios (working writing portfolio and showcase writing portfolio) on high school students’ writing achievement utilizing quasi-experimental design. The effectiveness of the two writing portfolios was tested by comparing pre-treatment and post-treatment samples using Independent Samples t test between both treatments. Regarding to .05 significance of level, the p value was compared to .025 for each side of 2-tailed research. The result showed p value .028 which was higher than .025. It signified that there was not significant different effect between both writing portfolios.Keywords: writing portfolios, working writing portfolio, students’ writing achievementAbstrak: Menulis dalam belajar mengajar Bahasa Inggris dianggap sebagai keterampilan yang sulit karena faktor internal dan eksternal. Penelitian ini bertujuan untuk mengetahui keefektifan dua portofolio menulis (Working Writing Portfolio dan Showcase Writing Portfolio) terhadap prestasi menulis siswa menengah atas dengan menggunakan desain quasi-experimental. Keefektifan kedua portofolio menulis tersebut diuji dengan membandingkan sampel nilai Pre-treatment dan Post-treatment menggunakan uji Independent Samples t antara kedua perlakuan. Merujuk pada tingkat signifikansi .05, nilai p dibandingkan dengan .025 untuk masing-masing bagian dari penelitian 2 arah. Hasil uji menunjukkan nilai p .028 yang lebih tinggi dari .025. Ini menunjukkan bahwa tidak ada perbedaan efek yang signifikan antara kedua portofolio tersebut.Kata kunci: portofolio menulis, portofolio karya tulis, prestasi menulis siswa